Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K201312, undergraduate, and graduate and professional levels.

Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The history of the U.S. criminal justice system is marked by racial inequality and sustained by present day policy. Large racial and ethnic disparities exist across the several stages of criminal legal processing, including in arrests, pre-trial detention, and sentencing and incarceration, among others, with Black, Latino, and Native Americans experiencing worse outcomes. The historical legacy of racial exclusion and structural inequalities form the social context for racial inequalities in crime and criminal justice. Racial inequality can drive disparities in crime, victimization, and system involvement. Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy synthesizes the evidence on community-based solutions, noncriminal policy interventions, and criminal justice reforms, charting a path toward the reduction of racial inequalities by minimizing harm in ways that also improve community safety. Reversing the effects of structural racism and severing the close connections between racial inequality, criminal harms such as violence, and criminal justice involvement will involve fostering local innovation and evaluation, and coordinating local initiatives with state and federal leadership. This report also highlights the challenge of creating an accurate, national picture of racial inequality in crime and justice: there is a lack of consistent, reliable data, as well as data transparency and accountability. While the available data points toward trends that Black, Latino, and Native American individuals are overrepresented in the criminal justice system and given more severe punishments compared to White individuals, opportunities for improving research should be explored to better inform decision-making.

Understanding and Offsetting Financial Barriers for Black Students in Science, Engineering, and Medicine: Programs, Partnerships, and Pathways: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The number of Black students in science, engineering, and medicine in the United States has remained disproportionately low over the past several decades. A number of reasons have been identified as contributing to these low numbers, including those related to finances. Financial considerations range from the most immediate - the ability of students to pay for their education and associated costs - to more structural concerns, such as inequities that created and have perpetuated a wealth gap between races and ethnic groups. On April 19-20, 2021, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine organized a virtual public workshop to examine financial barriers for Black students in science, engineering, and medicine, explore existing educational programs to them, and engage stakeholders in conversations about partnerships and policies that span academia, industry, and philanthropy. This publication summarizes the presentation and discussion of the workshop.

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.

Educational Pathways for Black Students in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
Academic preparation is critical to increase Black representation in Science, Engineering, and Medicine, but so, too, are such interrelated factors as providing mentoring and role models in sufficient numbers, adequately funding school and community support services, and analyzing the intentional and unintentional consequences of a range of policies and practices. To address these issues, the Roundtable on Black Men and Black Women of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on September 2 and 3, 2020. Titled \

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. But many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including: implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; higher teaching and advising loads; and fewer speaking invitations, among others. There are consequences from this underrepresentation of women for the nation as well: a labor shortage in many science, engineering, and medical professions that cannot be filled unless institutions and organizations recruit from a broad and diverse talent pool; lost opportunities for innovation and economic gain; and lost talent as a result of discrimination, unconscious bias, and sexual harassment. Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine reviews and synthesizes existing research on policies, practices, programs, and other interventions for improving the recruitment, retention, and sustained advancement into leadership roles of women in these disciplines. This report makes actionable recommendations to leverage change and drive swift, coordinated improvements to the systems of education, research, and employment in order to improve both the representation and leadership of women.

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors: Proceedings of a Symposium–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. Many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; and higher teaching and advising load, among others. A 2020 report by the National Academies of Sciences, Engineering, and Medicine (the National Academies), Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors, reviews the current state of knowledge of factors that drive underrepresentation of women in science, technology, engineering, mathematics, and medicine (STEMM) and provides an overview of existing research on policies, practices, programs, and interventions for improving the representation of women in these fields. On March 19, 2020, the National Academies held a virtual symposium to share key messages and findings from the report as well as hear from experts on the range of issues addressed in the study. This publication highlights the presentation and discussion of that event.

The Impacts of Racism and Bias on Black People Pursuing Careers in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Despite the changing demographics of the nation and a growing appreciation for diversity and inclusion as drivers of excellence in science, engineering, and medicine, Black Americans are severely underrepresented in these fields. Racism and bias are significant reasons for this disparity, with detrimental implications on individuals, health care organizations, and the nation as a whole. The Roundtable on Black Men and Black Women in Science, Engineering, and Medicine was launched at the National Academies of Sciences, Engineering, and Medicine in 2019 to identify key levers, drivers, and disruptors in government, industry, health care, and higher education where actions can have the most impact on increasing the participation of Black men and Black women in science, medicine, and engineering. On April 16, 2020, the Roundtable convened a workshop to explore the context for their work; to surface key issues and questions that the Roundtable should address in its initial phase; and to reach key stakeholders and constituents. This proceedings provides a record of the workshop.

The Science of Effective Mentorship in STEMM - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Mentorship is a catalyst capable of unleashing one's potential for discovery, curiosity, and participation in STEMM and subsequently improving the training environment in which that STEMM potential is fostered. Mentoring relationships provide developmental spaces in which students' STEMM skills are honed and pathways into STEMM fields can be discovered. Because mentorship can be so influential in shaping the future STEMM workforce, its occurrence should not be left to chance or idiosyncratic implementation. There is a gap between what we know about effective mentoring and how it is practiced in higher education. The Science of Effective Mentorship in STEMM studies mentoring programs and practices at the undergraduate and graduate levels. It explores the importance of mentorship, the science of mentoring relationships, mentorship of underrepresented students in STEMM, mentorship structures and behaviors, and institutional cultures that support mentorship. This report and its complementary interactive guide present insights on effective programs and practices that can be adopted and adapted by institutions, departments, and individual faculty members.

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.

Advancing Diversity in the US Industrial Science and Engineering Workforce: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Thousands of gifted individuals, including women and underrepresented minorities, remain a disproportionally small fraction of those in science, technology, engineering, and math (STEM) careers. Industry, as the largest employer category of those with STEM backgrounds, stands to benefit considerably from greater inclusion of women and underrepresented minorities in the workforce. However, nothing short of a game-changing environment must be created to harness the talent of those not fully represented in the STEM workforce. Advancing Diversity in the US Industrial Science and Engineering Workforce is the summary of a workshop held in May, 2012 by the National Academy of Engineering, focusing on the needs and challenges facing industry in particular, and it is intended to facilitate further discussion and actions to address these complex issues. The workshop provided a forum for leaders from industry, academia, and professional associations to share best practices and innovative approaches to recruiting, retaining, and advancing women and underrepresented minorities in the scientific and engineering workforce throughout the nation's industries.

Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics - National Academy of Engineering (The National Academies Press, 2012)
On August 8-12, 2010 the National Academy of Engineering (NAE), with funding from the National Science Foundation (NSF), convened the Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics (STEM), following the release of several reports highlighting the educational challenges facing minority males. The NSF recognized the need to gather input from research communities that focus on minority males about how to frame investigations of gender-based factors that impact learning and choice in STEM education (both at the precollege and higher education levels) and the workforce for minority males. There was particular interest in framing a research agenda to study how interactions between minority males and societal and educational systems (both formal and informal) encourage or discourage the young men's interest and persistence in STEM. In addition, NSF hoped to gain community input to inform the parameters of a future NSF research program that could effectively address minority male participation in STEM. The Colloquy was held at the Mt. Washington Conference Center in Baltimore, Maryland, with approximately 40 participants, most of them researchers in education, psychology, sociology, mathematics, and physics. Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics presents a summary of the Colloquy's breakout and plenary discussions, which addressed (a) research questions articulated in the breakout groups together with theories and methodologies to begin to address these questions; and (b) considerations for a potential research solicitation for the NSF, with major areas of inquiry concerning access, participation, and success for minority males in STEM. This report reflects the views of the individuals who participated in the plenary and breakout groups. It has been reviewed in draft form by persons chosen for their diverse perspectives and expertise in accordance with procedures approved by the National Academies' Report Review Committee. The purpose of this independent review is to provide candid and critical comments that will assist the institution in making its published report as sound as possible and to ensure that the report meets institutional standards for quality and objectivity.

Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Children are the foundation of the United States, and supporting them is a key component of building a successful future. However, millions of children face health inequities that compromise their development, well-being, and long-term outcomes, despite substantial scientific evidence about how those adversities contribute to poor health. Advancements in neurobiological and socio-behavioral science show that critical biological systems develop in the prenatal through early childhood periods, and neurobiological development is extremely responsive to environmental influences during these stages. Consequently, social, economic, cultural, and environmental factors significantly affect a child's health ecosystem and ability to thrive throughout adulthood. Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity builds upon and updates research from Communities in Action: Pathways to Health Equity (2017) and From Neurons to Neighborhoods: The Science of Early Childhood Development (2000). This report provides a brief overview of stressors that affect childhood development and health, a framework for applying current brain and development science to the real world, a roadmap for implementing tailored interventions, and recommendations about improving systems to better align with our understanding of the significant impact of health equity.

An American Crisis: The Growing Absence of Black Men in Medicine and Science: Proceedings of a Joint Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Black men are increasingly underrepresented in medical schools and in the medical profession. A diverse workforce is a key attribute of quality healthcare and research suggests that a diverse workforce may help to advance cultural competency and increase access to high-quality health care, especially for underserved populations. Conversely, lack of diversity in the health workforce threatens health care quality and access and contributes to health disparities. In this way, the growing absence of Black men in medicine is especially troubling, because their absence in medicine may have adverse consequences for health care access, quality, and outcomes among Black Americans and Americans overall. To better understand the factors that contribute to the low participation of Black men in the medical profession, facilitate discussion of current strategies used to increase their participation in medical education, and explore new strategies along the educational and professional pipeline that may have potential to increase participation in medicine, the National Academies of Sciences, Engineering, and Medicine and the Cobb Institute jointly convened a 2-day workshop in November 2017, in Washington, DC. This publication summarizes the presentations and discussions from the workshop.

Strengthening Forensic Science in the United States: A Path Forward - National Research Council (The National Academies Press, 2009)
Scores of talented and dedicated people serve the forensic science community, performing vitally important work. However, they are often constrained by lack of adequate resources, sound policies, and national support. It is clear that change and advancements, both systematic and scientific, are needed in a number of forensic science disciplines to ensure the reliability of work, establish enforceable standards, and promote best practices with consistent application. Strengthening Forensic Science in the United States: A Path Forward provides a detailed plan for addressing these needs and suggests the creation of a new government entity, the National Institute of Forensic Science, to establish and enforce standards within the forensic science community. The benefits of improving and regulating the forensic science disciplines are clear: assisting law enforcement officials, enhancing homeland security, and reducing the risk of wrongful conviction and exoneration. Strengthening Forensic Science in the United States gives a full account of what is needed to advance the forensic science disciplines, including upgrading of systems and organizational structures, better training, widespread adoption of uniform and enforceable best practices, and mandatory certification and accreditation programs. While this book provides an essential call-to-action for congress and policy makers, it also serves as a vital tool for law enforcement agencies, criminal prosecutors and attorneys, and forensic science educators.

Long-Term Impacts of COVID-19 on the Future Academic Careers of Women in STEM: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On March 23-24, 2022, the National Academies of Sciences, Engineering, and Medicine held a virtual workshop to explore the long-term impact of COVID-19 on the future careers of women in STEM. Workshop participants represented multiple sectors (i.e., higher education, government, and non-profit) as well as various career paths and stages (e.g., assistant, associate, and full professors; graduate students; program officers; directors; and policy advisors). The two-day workshop convened experts and leaders to outline a national research agenda that ensures academic institutions and federal agencies are able to monitor and mitigate the long-term negative impacts of the pandemic on the career trajectories, job stability, and leadership roles of women - especially women of color 2014 in STEM. This publication highlights the presentation and discussion of the workshop.

The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The spring of 2020 marked a change in how almost everyone conducted their personal and professional lives, both within science, technology, engineering, mathematics, and medicine (STEMM) and beyond. The COVID-19 pandemic disrupted global scientific conferences and individual laboratories and required people to find space in their homes from which to work. It blurred the boundaries between work and non-work, infusing ambiguity into everyday activities. While adaptations that allowed people to connect became more common, the evidence available at the end of 2020 suggests that the disruptions caused by the COVID-19 pandemic endangered the engagement, experience, and retention of women in academic STEMM, and may roll back some of the achievement gains made by women in the academy to date. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine identifies, names, and documents how the COVID-19 pandemic disrupted the careers of women in academic STEMM during the initial 9-month period since March 2020 and considers how these disruptions - both positive and negative - might shape future progress for women. This publication builds on the 2020 report Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine to develop a comprehensive understanding of the nuanced ways these disruptions have manifested. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine will inform the academic community as it emerges from the pandemic to mitigate any long-term negative consequences for the continued advancement of women in the academic STEMM workforce and build on the adaptations and opportunities that have emerged.

Improving Representation in Clinical Trials and Research: Building Research Equity for Women and Underrepresented Groups - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The United States has long made substantial investments in clinical research with the goal of improving the health and well-being of our nation. There is no doubt that these investments have contributed significantly to treating and preventing disease and extending human life. Nevertheless, clinical research faces a critical shortcoming. Currently, large swaths of the U.S. population, and those that often face the greatest health challenges, are less able to benefit from these discoveries because they are not adequately represented in clinical research studies. While progress has been made with representation of white women in clinical trials and clinical research, there has been little progress in the last three decades to increase participation of racial and ethnic minority population groups. This underrepresentation is compounding health disparities, with serious consequences for underrepresented groups and for the nation. At the request of Congress, Improving Representation in Clinical Trials and Research: Building Research Equity for Women and Underrepresented Groups identifies policies, procedures, programs, or projects aimed at increasing the inclusion of these groups in clinical research and the specific strategies used by those conducting clinical trials and clinical and translational research to improve diversity and inclusion. This report models the potential economic benefits of full inclusion of men, women, and racial and ethnic groups in clinical research and highlights new programs and interventions in medical centers and other clinical settings designed to increase participation.

Transforming Trajectories for Women of Color in Tech - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Demand for tech professionals is expected to increase substantially over the next decade, and increasing the number of women of color in tech will be critical to building and maintaining a competitive workforce. Despite years of efforts to increase the diversity of the tech workforce, women of color have remained underrepresented, and the numbers of some groups of women of color have even declined. Even in cases where some groups of women of color may have higher levels of representation, data show that they still face significant systemic challenges in advancing to positions of leadership. Research evidence suggests that structural and social barriers in tech education, the tech workforce, and in venture capital investment disproportionately and negatively affect women of color. Transforming Trajectories for Women of Color in Tech uses current research as well as information obtained through four public information-gathering workshops to provide recommendations to a broad set of stakeholders within the tech ecosystem for increasing recruitment, retention, and advancement of women of color. This report identifies gaps in existing research that obscure the nature of challenges faced by women of color in tech, addresses systemic issues that negatively affect outcomes for women of color in tech, and provides guidance for transforming existing systems and implementing evidence-based policies and practices to increase the success of women of color in tech.